2015
DOI: 10.1007/s11743-015-1737-z
|View full text |Cite
|
Sign up to set email alerts
|

Using the Scanning Fluid Dynamic Gauging Device to Understand the Cleaning of Baked Lard Soiling Layers

Abstract: Extended or repeated heating of food fats promotes polymerisation reactions that produce difficult-to-remove soil layers. Cleaning of these baked-on/burnt-on fat deposits was investigated using model layers generated by baking lard on 316 stainless steel discs. Rigorous characterisation of the layer material was difficult, as it was insoluble in most solvents. Cleaning was studied using the scanning fluid dynamic gauging technique developed by Gordon et al. (Meas Sci Technol 21:85–103, 2010), which provides no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The cleaning mechanism and behaviour is ultimately determined by the nature and microstructure of the soil. For example, Ali et al (2015a) studied the cleaning of polymerised lard soil layers on stainless steel and reported that solutions of TX-100 and LAS at pH 10.4-11 promoted solution ingress and soil detachment at the soil-substrate interface, while CTAB promoted penetration through the soil layer (rather than promoting ingress as observed in this work). These differences illustrate how, like coatings to prevent deposition and fouling, detergent solutions need to be matched to the soil.…”
Section: Effect Of Surfactantmentioning
confidence: 59%
See 3 more Smart Citations
“…The cleaning mechanism and behaviour is ultimately determined by the nature and microstructure of the soil. For example, Ali et al (2015a) studied the cleaning of polymerised lard soil layers on stainless steel and reported that solutions of TX-100 and LAS at pH 10.4-11 promoted solution ingress and soil detachment at the soil-substrate interface, while CTAB promoted penetration through the soil layer (rather than promoting ingress as observed in this work). These differences illustrate how, like coatings to prevent deposition and fouling, detergent solutions need to be matched to the soil.…”
Section: Effect Of Surfactantmentioning
confidence: 59%
“…Whereas denatured whey proteins were reported to swell and erode in alkali, gelatin and egg proteins both swelled but both require shear forces to effect removal (Gordon et al, 2010;Perez-Mohedano et al, 2016). Ali et al (2015a) observed little swelling with burnt oil soils in aqueous cleaning solutions and removal of these was characterised by a 'cohesive blistering' mechanism.…”
Section: Soil Adhesion Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to analyze the mechanism of oily soil removal during washing, many studies have been conducted by applying various methods such as molecular dynamics simulations 22 , combined molecular dynamics and quantum mechanics 23 , lattice Monte Carlo simulations 24 , confocal laser scanning microscopy 25 , a scanning fluid dynamic gauging device 26 , and the quartz crystal microbalance technique 27 .…”
Section: Introductionmentioning
confidence: 99%